Accuracy of 64-multidetector computed tomography in diagnosis of adnexal tumors - Gatreh-Samani Fatemeh; Tarzamni Mohammad; Olad-Sahebmadarek Elaheh; Dastranj Ali; Afrough Aimaz (BMC, 2011)
Abstract Background Adnexal cancers are in fifth place among the tumors with the highest mortality in the female population. The aim of the present study was to evaluate the accuracy of Multi-detector computed tomography (MDCT) on a 64-multislice CT scanner in the detection and differentiation of adnexal masses stages. Methods During the present prospective study, 95 women with a primary diagnosis of ovarian mass in base of clinical examination and ultrasonographic findings underwent preoperative evaluation by a 64-slice MDCT with a section thickness of 0.6 mm, 50% overlap and reconstructed images. Afterward, results of MDCT were compared with surgical and histopathological findings, and the sensitivity, specificity, positive and negative predictive value and accuracy were determined. Results The mean age of patients was 48.63 ± 13.93 years. MDCT diagnosed 25 (26.3%) masses to be benign and 70 (73.7%) to be malignant (sensitivity, specificity, positive and negative predictive value and accuracy were 92.8%, 88.0%, 95.5%, 81.4% and 91.5% respectively). The sensitivity and specificity of MDCT in determining local extension was 72.2% and 93.4% respectively. And the sensitivity and specificity of MDCT in determining peritoneal seeding and liver extension was 81.8% and 93% respectively. Estimated stage was significantly agreed with the surgical (Cohen's Kappa (κ) = 0.891) and histopathological findings (κ = 0.858). Conclusion MDCT is a highly sensitive and specific diagnostic method in evaluation of adnexal masses and successfully stage the tumor in consistent with surgery and histopathology.